Making movies: from script to screen - Bobker, Lee R. 4 0 16; Marinis, Louise; 5 (New York, Harcourt Brace Jovanovich, 1973)
Text and illustrations describe the equipment, budgeting, directing, and editing techniques, and other aspects of film production for beginners.
Includes bibliographies.
Keywords: 2 -- 0; 6; Production and direction.;Production and direction. -- Cinematography.;Amateur films;Amateur motion pictures.;Motion pictures -- 20; 20; 2